Numerical and Experimental Protective Performance Evaluation of Sacrificial Member Effects on the Protective Structures. Issue 3 (November 2021) - Kwon, Jihye; Han, Seungsu; Kim, Sungkon
Abstract: Principal objectives of the protective design are on protecting life, property, facility, system device and operations by developing protective design measures that reduce threat level and vulnerability while enhancing structural resilience. Protective design procedure against blast hazard would be accomplished with the threat identification, risk-based assessment, and designing the members and structures based on the proper design requirements. Considerable necessity before the protective design is to find out the various measures reducing the blast effect such as security measures, architectural configuration, and mitigation schemes without any structural strengthening the structure itself. This paper addresses the mitigation scheme to reduce the blast overpressure in general, and then a specific barrier type is introduced as sacrificial structures with the performance verification. The general schemes to reduce the blast pressure by installing barriers is mainly using RC type structures which have typical shapes and sizes. This barrier type has advantages both on installing easiness and cost. In the barrier type sacrificial wall structure, instead of using the normal RC structures, enhanced-cement concrete and composites are useful to improve protective performance and scabbing of the back surface of the RC walls. A series of the wall type RC barriers are modeled and fabricated to investigate and verify blast pressure migration and protective performance based on theoretical and numerical analysis.